Optimization of Ultrasonic-Assisted Extraction of Polyphenolic and Flavonoids from Labisia pumila - Jessinta, Sandanasamy; M. M., Yusoff; Jolius, Gimbun (Trans Tech Publication, 2017)
This work presents an optimization study of polyphenol extraction from L. pumila with aid of sonication. The polyphenol content was evaluated using Singletons method and aluminium chloride colorimetric assay. The two level factorial design 2LF was used to screen the significance of the extraction parameters. The results proposed that the polyphenols extraction are mainly affected by the total solid ratio TSR and residence time. The highest flavonoid content of 31.79 mg QE/ g DW and phenolic content of 19.65 mg GA/g DW was obtained from 80% and 10% aqueous ethanol EtOH, respectively via 2LF design. Three most important parameters TSR, residence time and amplitude were then further optimized thru central composite design. The highest simultaneous flavonoid 21.77 mg QE/ g DW and phenolic 21.86 mg GA/g DW extraction yield were attained from the probe sonicator extraction with desirability of 0.998 at 10% aqueous EtOH with TSR 0.01, residence time of 13 min and amplitude of 55%.